2017
DOI: 10.1016/s2215-0366(17)30159-1
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and mental illness-related morbidity and resilience: a systematic review and meta-analysis

Abstract: Background: Studies on the association between income inequality and mental have shown mixed results, probably due to methodological heterogeneity. By dealing with such heterogeneity through a systematic review and meta-analysis, we examine the relationship between income inequality, mental health problems, use of mental health services, and resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 45 publications
10
102
1
3
Order By: Relevance
“…A review of studies on the association of income inequality and a range of mental health related outcomes reported heterogeneous findings, with about one third of studies observing a positive association between income inequality and the prevalence or incidence of mental health problems, one third observing mixed results for different subgroups, and one third observing no association 5 . Depression was one of the mental health outcomes considered in studies showing a positive association with income inequality.…”
mentioning
confidence: 99%
“…A review of studies on the association of income inequality and a range of mental health related outcomes reported heterogeneous findings, with about one third of studies observing a positive association between income inequality and the prevalence or incidence of mental health problems, one third observing mixed results for different subgroups, and one third observing no association 5 . Depression was one of the mental health outcomes considered in studies showing a positive association with income inequality.…”
mentioning
confidence: 99%
“…There are even studies finding no linkage between income inequality and environmental quality [45,46]. Some studies found that income anticipations could affect mental health and that income inequality generally damaged subjective well-being and led to psychological problems [18,[47][48][49][50][51]. Further, Velek and Steg (2007) proposed that psychological factors were important in promoting sustainable consumption of natural resources [52].…”
Section: Introductionmentioning
confidence: 99%
“…no. reviews contributing termsReviews contributing terms‘Place’Place of residence5No-5No-5[1014]‘Race’Race / ethnicity / culture / language3Yes →69No-9[11, 1522]Occupation6No-6No-6[11], [13], [16], [23], [24], [25]‘Gender’Gender / sex1Yes →67No-7[16], [17], [18], [19], [26], [27], [28]Religion0Yes →11Yes →23[17, 29, 30]Education7No-7No-7[11, 13, 16, 24, 25, 31, 32]‘SES’Socio-economic status12No-12No-12[11], [13], [15], [23], [24], [25], [31], [32], [33], [34], [35], [36]Social capital0Yes →11Yes →45[17, 3740]Other category not encompassed by PROGRESS-Plus6No-...…”
Section: Resultsmentioning
confidence: 99%